Impact of Community Empowerment Training on Cadets' Work-Study Balance and Leadership Development in Jakarta's Maritime Education Institutions - Boy Laksmana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This qualitative study investigates the impact of community empowerment training on cadets' work-study balance and leadership development within Jakarta's maritime education institutions. Through in-depth interviews with 10 cadets engaged in internships alongside their academic studies, the study identifies key themes. These include the development of time management skills, enhancement of communication abilities, and opportunities for leadership growth facilitated by the training programme. Findings highlight the crucial role of practical skills development in equipping cadets to manage academic and professional responsibilities effectively. Recommendations for educational practices include integrating practical skills training, expanding leadership initiatives, fostering industry collaboration, implementing feedback mechanisms, and promoting lifelong learning among cadets and faculty. These initiatives aim to prepare cadets to meet the challenges of the maritime industry and contribute to its sustainable growth. The study contributes to enhancing educational strategies in maritime education and underscores the importance of holistic development in shaping future maritime leaders